2019
DOI: 10.1145/3359242
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Review

Abstract: As video game press ("experts") and casual gamers ("amateurs") have different motivations when writing video game reviews, discrepancies in their reviews may arise. To study such potential discrepancies, we conduct a large-scale investigation of more than 1 million reviews on the Metacritic review platform. In particular, we assess the existence and nature of discrepancies in video game appraisal by experts and amateurs, and how they manifest in ratings, over time, and in review language. Leveraging these insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Moreover, by testing the effects of different factors, including valance, volume, and consistency of reviews, researchers also identified influencer reviews as the determinant of game sales [5][6]. Other research also demonstrates that influencer reviews could predict the video game's reputation in the long term [7].…”
Section: Influencer Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, by testing the effects of different factors, including valance, volume, and consistency of reviews, researchers also identified influencer reviews as the determinant of game sales [5][6]. Other research also demonstrates that influencer reviews could predict the video game's reputation in the long term [7].…”
Section: Influencer Reviewsmentioning
confidence: 99%
“…user-generated content is expected to be more authentic and self-expressive than mass-media creation, which relies heavily on the advertiser and is full of promotional artifacts [14]. Santos et al also recognize that user reviews are less technical, more readable, and more emotional compared to expert critics of video games [7]. In this way, the review content can be relatable to major audiences.…”
Section: User-generated Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Huang et al [30] used LDA to identify various themes in Yelp reviews of restaurants, including service, value, decoration, and health. Feuerriegel et al [31] analyzed the impact of topics in corporate press releases on stock market returns, whereas Santos et al [32] applied LDA to assess disparities in video game evaluations by experts and amateurs.…”
Section: B Topic Modeling For Online Reviewsmentioning
confidence: 99%
“…The third section is an application of the methods. 1, 552, 750 public reviews are collected by 40, 665 items of theplatform Metacritic (Kasper et al 2019;Santos et al 2019). 218 EBI are detected and matched.…”
Section: Introductionmentioning
confidence: 99%